Qu’est-ce qu’une « race animale pure » ? - Patricia Pellegrini; Marie-Dominique Ribereau-Gayon (Revue d'ethnoécologie)
In France, studies on farm animal breeding in various disciplines (anthropology, sociology, history, zootechny, etc.) extensively use the notion of “race”. However, the technical process of race construction has hardly been considered so far. Our analysis of the case of the Bordelaise breed (deemed extinct since WW2 and under reconstruction since the 1990s) shows how the local bovine population was established as a race and its standard defined and modified throughout the 19th c. Commonsense usually explains the homogeneity of some groups of animals by their adaptation both to their environment and to human practices. Our purpose here is, on the contrary, to evidence that the concepts of “race” and “pure race” actually mask a deliberate, minute and elaborate process of selection. For example, cattle’s physical features can be modified at will through the system of factors for qualitative and quantitative selection criteria. When extended to the extreme, the process of assessment and selection of individuals leads to inadequacy and extinction.Note that, for lack of equivalent for “breed” in French, the notion of “race” is far more extensive than in English. Consequently, the reference to biological races is much weaker in English than in French.